National Geographic traveler. Barcelona - Simonis, Damien; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2009)
Presents a guide to traveling in Barcelona, and provides in-depth descriptions and background information on famous sites, historical and cultural notes, hotels, restaurants, and shops. Includes maps and photographs.
Includes index.
Map on inside covers.
Adult
Keywords: Barcelona (Spain) -- Guidebooks; Barcelona (Spain) -- Description and travel; Barcelona (Spain) -- Guidebooks; Barcelona (Spain) -- Description and travel